Characterization of Active Carbon Prepared from Coconuts Shells using FTIR, XRD and SEM Techniques - Bakti, Andi Ikhtiar; Gareso, Paulus Lobo (Jurnal Ilmiah Pendidikan Fisika Al-Biruni, 2018)
Activated carbon is produced from coconut shells through physical and chemical activation. With pyrolysis method, the optimum activation temperature for physics activation is 600oC, and for chemical, activation is to soak it in activator ZnCl2 10% and Na2Ca3 10%. Activated carbon was analyzed by Fourier Transformation Infrared (FTIR) and X-ray Diffraction (XRD) methods. The FTIR result showed that the coconut shells succeeds in becoming carbon. The XRD results confirm the existence of several phases of crystals like graphite around the peaks of 36o and 44o, there are two wide diffraction peaks and can be interconnected with carbon and graphite content. The SEM result showed that the carbonization of pyrolysis and activation processes created porosity and a large surface area for absorption